Análise de bacia sedimentar e quimioestratigrafia do Grupo Bambuí em Minas Gerais - Gabriel Jube Uhlein (2017)
For a better understanding about the evolution of the Bambuí basin in the state of Minas Gerais, different key-areas were studied from the point of view of sedimentology, stratigraphy and geochemistry. Each of these areas set up an important piece of the puzzle occurred in the late Neoproterozoic. The Carrancas Formation outcrops at the southernmost Bambuí basin and yield stratigraphic characteristics of rift-like basin deposited above the cratonic basement. Together with carbon isotopic data, it is interpreted a correlation with the Tijucuçu Sequence (Macaúbas Group) and a Cryogenian age (interglacial) for them, both being deposited during with the isotopic event Keele peak occurred globally at ca. 680 Ma. Thus, the Carrancas Formation was deposited previous to the glaciogenic event occurred over the São Francisco craton and cannot be correlated to the glaciogenic Jequitaí Formation. The Samburá Formation outcrop at the southwest Bambuí basin and shows evidence to support a fan delta sedimentation likely concomitant to the main phase of the Brasilia belt orogenic buildup and an the initial stage of Bambuí basin evolution. Detrital zircon U-Pb date indicate a maximum sedimentation age of ca. 630 Ma, while placing of external nappes from the Brasilia belt over the Samburá Formation at ca. 560 Ma constrains its minimum deposicional age. Further to the North, the Lagoa Formosa Formation is interpreted as being deposited as deep marine turbidites during progradation and basin shallowing. Detrital zircon U-Pb indicates maximum depositional age at ca. 560 Ma, suggesting deposition after the placing of external nappes anda t the late stage of Bambuí basin. Carbonates from the Lagoa Formosa Formation provide clues for probable Ediacaran-Camrian transition occurred in the upper Bambuí Group. The southwestern margin of the Bambuí basin shows evidences to support a foreland basin evolution initiated at ca. 630 Ma, lasting for about 100 million years and spanning the whole Ediacaran and lower Cambrian Periods. At the north central Minas Gerais state, between the cities of Januária and Jaíba, the Bambuí Group outcrops from base to top and show low weathering degree and absence of deformation or metamorphism. From a sequence stratigraphic study, four complete sedimentary sequences and one incomplete sequence were established for the Bambuí Group. The occurrence of carbonatic and siliciclastic highstand systems tracts suggest that base level variations are not the only controlling factor to dicatate the sedimentation nature. From carbon isotopic data, a complete 13C curve for the whole Bambuí Group is presented for the first time. The highly positive values in the middle Bambuí Group stand for about 350 m from the base of the Serra de Santa Helena Formation, with a return to low positive values in the Jaíba Member carbonates. Highly isotopically enriched carbonates also occur in other basins over the São Francisco craton and its northern margin, and the possible correlation between them suggest a wider frame for the cause os such isotopic signal. It is suggested that the extreme positive values ocorring in the Bambuí basin and other basins may be a product of basin restriction and stratified ocean together with great productivity increase during a specific period of ocean fertilization. These isotopic values were probably amplified by a reservoir effect controlled by the paleogeography of continental blocks during the amalgamation of the West Gondwana close to the Ediacaran-Cambrian limit.